Literature 1997, Part 1 - Burkhardt, Gernot; Resch-Esser, Ursula; Hefele, Herbert; Heinrich, Inge; Hofmann, Wilfried; Matas, Vladimir R.; Schmadel, Lutz D.; Wielen, Roland; Zech, Gert (Astronomy and astrophysics abstracts, 1998)
Astronomy and Astrophysics Abstracts is devoted to the recording, summarizing and indexing of astronomical publications throughout the world. Two volumes are scheduled to appear per year. Volume 67 records 10,903 papers covering besides the classical fields of astronomy and astrophysics such matters as space flights related to astronomy, lunar and planetary probes and satellites, meteorites and interplanetary matter, X rays and cosmic rays, quasars and pulsars. The abstracts are classified under more than one hundred subject categories thus permitting quick surveying of the bulk of material published on the same topic within six months. For instance, this volume records 119 papers on minor planets (subject category 098), 155 papers on supernovae (subject category 125), and 554 papers on cosmology (subject category 161). Volume 67 has been recorded by means of a local network yielding copies ready for photocomposition